Understanding how children develop and regulate feelings of chronic shame - Tsimopoulou, Ioanna (Interdisciplinary applications of shame/violence theory, 2022)
This chapter brings together different theories and models about how children develop and regulate feelings of chronic shame. The emergence of chronic shame is examined in the context of children’s attachment relationships and experiences of childhood maltreatment. The long-term difficulties that children might face with chronic shame are discussed, and the maladaptive strategies they are likely to use to regulate their overwhelming shame feelings are explored. We focus on how violence towards the self and/or other people can be used as a shame regulation strategy, and a clinical example is provided to further elucidate the link between chronic shame and violent or other challenging behaviour in children. Finally, a reflective account is included with observations from clinical practice and ideas on how to raise awareness about the nature and consequences of chronic shame and the need to break the intergenerational cycles of shame and violence.